A grammarian's view of negation: Nāgeśa's Paramalaghumañjūṣā on nañartha - Lowe, J; Benson, J (Springer, 2022)
The theory of negation developed in the grammatical-philosophical system of later Vyākaraṇa remains almost entirely unstudied, despite its close links with the (widely studied) approaches to negation found in other philosophical schools such as Nyāya and Mīmāṃsā, and despite its consequent importance for a comprehensive understanding of the theory of negation in ancient India. In this paper we present an edition, translation and commentary of the relevant sections of Nāgeśa’s Paramalaghumañjūṣā, a concise presentation by the final authority of the Pāṇinian tradition, together with an explanatory introduction outlining the grammarians’ theory of negation and its relations particularly with the Nyāya theory of negation.